Huge Pulsatile Sternal Mass - Nornazirah Azizan; Firdaus Hayati; Ho, Hui Lian; Siti Zubaidah Sharif (2020)
A 46-year-old woman presented with a huge, hard sternal mass with a one -year history. The size of the mass has been progressively increasing from an initial size of a table tennis ball. It was dull and aching in nature with a sensation of heaviness, which affected her daily life activities and made her seek medical attention. The mass was associated with skin discoloration and contact bleeding. There was no fever. Clinically, despite being hard and fixed, it tended to pulsate with bruit on auscultation [Figure 1]. She had a total thyroidectomy for a multinodular goiter 10 years prior, but defaulted follow-up soon after the surgery. She was on thyroid replacement therapy, but decided to stop taking it for the past two years due to a logistic issue.